Da magia ao desencanto: emoções e comportamento, de clientes, no consumo em restaurantes - Silveira, Paula Sut da (2019)
In the marketing discipline, scholars argue that the kind of emotion a person feels is relevant and evident in human consumption. However, the literature review on emotions and consumption showed the polarity of the dimensions of emotions, which can be positive or negative, which is of great importance, since emotion is related to consumer decision-making. Based on their emotions, people form or reject social connection and develop, maintain, increase, or avoid their commitments to social structures and cultures. For this reason, emotions play an important role in human activity for society. The present study consisted of investigating the different types of emotions and connecting them with positive and negative affection. From the affections, the behavior for the repurchase or abandonment (migrate to other competitor), in relation to the service provider company, in this case within the restaurant scenario. Twelve individuals were interviewed from June to August 2019, resulting in 24 reports of positive and negative affect experiences in 23 different restaurants, 2:30 hours of recording and 32 transcribed pages. From Laros e Steemkamp's (2005) hierarchical model, the findings of this research can confirm the emotions studied by the authors, and add specific emotions within the restaurant setting. These findings are unique within the retelling qualitative methodology for out-of-home food, which this author considers integrated with the Brazilian consumer behavior. The result of this work will reaffirm that positive emotions lead consumers to share the positive experience with others and tend to become frequent in that establishment. However, negative emotions can result in complaining behavior, or even without complaining, the consumer will share his experience to another potential consumer and abandon the establishment. The emotion of negative affect can be aggravated by the situation where the consumer is involved in a celebration event. As a contribution of this study, are listed in the course of a specific chapter, the main items that could suggest managerial look and effort for improvement actions in the achievement of positive affection of consumers.